Áreas protegidas urbanas e conservação de um ecótone Cerrado-Mata Atlântica - Eric Reno Souza Xavier (2018)
The destruction of biomes Mata Atlântica and Cerrado has taken alarming dimensions, and urban sprawl has been a relevant factor for this scenario. In this study we analyzed the role of protected areas (APs) in the municipality of Belo Horizonte for the conservation of an ecotone Cerrado-Mata Atlântica, focusing in their roles to hold back existing urban threats that compromises important fragments of these two hostspots. With documental analyzes we evaluated how many green protected areas exist in the municipality, who are responsible for them, and their creation goal. With vegetation cover classification from satellite imagery we verified the potential to conserve the vegetation in Belo Horizonte municipality. We found out 98 protected areas in the municipality, with four different levels of management, and that have the goal to conserve biodiversity. They comprehend more than 10% of the municipality territory, conserve an area of 1.587 ha of Mata Atlântica and arboreal and arbustive phytophysiognomies of Cerrado, besides 1.603 ha of grassland vegetation, that includes campos rupestres or campos limpos and planted areas. The percentage of vegetation arboreal and arbustive or grasslands present in the APs (95%) indicates that they have potential to conserve the ecotone, even if they comprehend small areas with exotic vegetation or if they are altered areas. Although the larger areas of native grasslands concentrate in south of the municipality, other areas with grasslands, like pasture, could be recovered aiming the conservation of species from Cerrado or Mata Atlântica.